2020
DOI: 10.3390/su12093562
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Barriers to the Community Acceptance of Wind Energy: Lessons Learnt from a Comparative Analysis of Best Practice Cases across Europe

Abstract: Empirical evidence has shown that local community opposition is one of the key obstacles for new wind energy development. Consequently, the community acceptance of renewables, such as wind energy, has become a crux for Europe in both achieving and going beyond its renewable energy targets. Significant academic literature has already been devoted to conceptualising the community acceptance of wind energy. This article builds on the existing research by showcasing how regions and municipalities across Europe hav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 11 publications
(15 reference statements)
0
6
0
1
Order By: Relevance
“…Municipalities should be strengthened in using this instrument. They should have access to respective advisory services [116,120] which could be linked to existing offers, developed by organizations with a high level of expertise, such as the German Competence Center for Nature Conservation and Energy or the Specialist Agency for Onshore Wind Energy.…”
Section: Decision Makingmentioning
confidence: 99%
See 1 more Smart Citation
“…Municipalities should be strengthened in using this instrument. They should have access to respective advisory services [116,120] which could be linked to existing offers, developed by organizations with a high level of expertise, such as the German Competence Center for Nature Conservation and Energy or the Specialist Agency for Onshore Wind Energy.…”
Section: Decision Makingmentioning
confidence: 99%
“…Maleki-Dizaji et al [120] have shown that financial participation that contributes to the creation of regional or local added value is one of the most common success factors for community acceptance. This finding is directly in line with our results.…”
Section: Increased Local Added Valuementioning
confidence: 99%
“…The larger size of the new projects, their physical impacts on the environment and biodiversity, their proximity to residential areas, and the lack of consultation and involvement of the local communities have contributed to eroding the support for, and acceptance of, renewable energies in Germany (Leiren et al 2020). This has generated a lack of trust, becoming a barrier to the success of new projects (Maleki-Dizaji et al 2020). Recently, Germany has again modified its Renewable Energy Act (EEG), aiming to improve the level of acceptance of renewable energy projects by citizens.…”
Section: The Pioneers: Denmark and Germanymentioning
confidence: 99%
“…] this democratization of energy will alleviate energy poverty and protect vulnerable citizens" (European Commission, 2019, p. 12). Much of previous research on social and economic benefits of community energy projects has focused on their impact on renewables growth (Caramizaru and Uihlein, 2020;Verde and Rossetto, 2021), public acceptance (Fast, 2013;De Luca et al, 2020;Maleki-Dizaji et al, 2020) or regional economic development (Callaghan and Williams, 2014;Kunze and Becker, 2014;Gancheva et al, 2018). To date, there is little empirical research on the potential of renewable electricity-producing community energy projects to protect and benefit vulnerable consumers and alleviate energy poverty, particularly in the German energy policy context.…”
Section: Introductionmentioning
confidence: 99%